Propagação in vitro de portaenxertos de pessegueiro Flordaguard e GxN-9 - Ritterbusch, Cristina Weiser (2013)
The fruitful lump such as peaches, has shown annual growth of both production and consumption in Brazil and Rio Grande do Sul (RS) the leading national producer. However compared to other Brazilian states productivity in RS is considered low and one of the factors is the lack of genetic quality and health of propagation material. This is due in part to the means of acquiring rootstocks, which are derived from discarded lumps by canning industries, among other factors causing imbalance between plants in the orchard. Thus vegetative propagation from the micropropagation constitutes an alternative multiplication of rootstocks, obtaining a large number of plants in a short period of time compared with the traditional method used. Thus developing protocols for vegetative propagation may contribute to the process of producing seedlings prunaceas in southern Brazil. Therefore, the aim of this study was to optimize the in vitro multiplication rootstocks' Flordaguard 'and' GxN-9 'and in vitro rooting and acclimatization of shoots from the rooting medium with the rootstock' GxN-9 '. To this end, the work was divided into two chapters, one on the in vitro multiplication of rootstock "Flordaguard 'and the second concerning the multiplication, rooting and acclimatization of the rootstock' GxN-9 '. In the first chapter means were tested MS (1/2N) and Himedia, type and orientation of the explant and the concentration of BA. In the second chapter aimed to evaluate the effect of the concentration of cytokinins (BA and KIN) and the source and amount of carbohydrate in the multiplication phase, the influence of IBA concentration on rooting and acclimatization of plants. To rootstock 'Flordaguard' MS medium (1/2N) was superior to Himedia both to number of shoots per explant for growth as these. The growth of the sprout was highest in semi-solid medium with a liquid medium in comparison with semi-solid medium without liquid medium. However the type and orientation of the explant did not influence the number and length of shoots formed. For BA concentration, 3 mg L-1 induces greater number of shoots (4.02) but the greatest growth (1.85) of shoots occurred until the concentration of 0.5 mg L-1 BA. In the multiplication of 'GxN-9' explants cultured in medium containing 0.4 mg L-1 BA have the highest number of shoots the largest growth was achieved at concentrations of 0.2 mg L-1 BA + 0.2 mg L-1 KIN (0.72). Now, as to the source and concentration of carbohydrate, 30 g L-1 sucrose is sufficient for the greatest number of shoots. As regards à rooting phase in vitro and acclimatization induction, shoots cultivated in culture medium with 1.2 mg L-1 IBA, they had 100% rooting, well as of plants survivors in the phase of acclimatization.